70.9k views
2 votes
PLEASE HELP MEE THIS QUESTION IS THE LAST ONE I NEED TO GET RIGHT TO PASS PLS!!

PLEASE HELP MEE THIS QUESTION IS THE LAST ONE I NEED TO GET RIGHT TO PASS PLS!!-example-1

2 Answers

0 votes

Answer:

see explanation

Explanation:

The answer is -
(2)/(17) , since


(-(2)/(17)) ^(3)

= -
(2)/(17) × -
(2)/(17) × -
(2)/(17)

=
(4)/(289) × -
(2)/(17)

= -
(8)/(4913)

that is


\sqrt[3]{-(8)/(4913) } = -
(2)/(27) because
(-(2)/(17)) ^(3) = -
(8)/(4913)

User Igor Gilyazov
by
4.6k points
1 vote

Explanation:

the root cube of -8/4913 when transferred to the side -2/17, it becomes it's cube .

means the "___ " will be (-2/17)³= -8/4913.

hope this helps you

User S Jagdeesh
by
4.7k points